Margem de potência reativa em tempo real equacionamento para cálculo direto da curva VQ - Leticia Caixeta Nunes (2019)
This master thesis addresses the topic Voltage Stability regarding Electric Power Systems monitoring for real-time operation. More specifically, the work presents a methodology proposal, by means of electrical network equations, to calculate the VQ curve and the voltage and reactive power at its minimum point. The developed equations can be applied to real-time network equivalents, expanding the methodology use to large-scale systems. The objective is that the information brought by the VQ curve, such as the Reactive Power Margin, can be calculated in real-time, in the same way it is done for the PV curve, which Active Power Margin is obtained from well-known equations. The proposed methodology is applied for two network equivalents obtained from the IEEE 14 bus test system: an equivalent for real-time purposes and an analytical reference equivalent. To calculate real-time equivalent, two current and voltage samples are considered after load increment. The analytical equivalent is based on the Thévenin theorem. The results are compared with those obtained from successive power flow simulations considering a fictitious synchronous generator connected to the studied bus. In addition, the proposed equations are also applied to real-time voltage and current measurement data collected from a busbar of the National Interconnected System. The results show that the values obtained by the methodology are consistent, emphasizing its significant contribution to power system operation.